Developing a Canva-Based Interactive Social Science E-Book Integrated with Jambi Local Wisdom for Fifth-Grade Students - Aura Putri, Tazkiya; Nasyariah Siregar; Nisa Aulia (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2026)
Digital learning media play an important role in supporting meaningful learning in elementary education, particularly in integrated Natural and Social Science (IPAS) subjects. Interactive e-books enable learning materials to be presented in more engaging, visual, and contextual ways, helping students understand abstract concepts through real-life experiences. Digital media are especially suitable for IPAS materials requiring visualization and interactive exploration, such as ecosystems, biodiversity, environmental processes, and local cultural practices. This study aimed to develop a Canva-based interactive e-book integrated with Jambi local wisdom for Grade 5 elementary students and examine its feasibility and practicality. The study employed a Research and Development (R&D) approach using the 4-D model: Define, Design, Develop, and Disseminate. The research involved 25 Grade 5 students. Data were collected through expert validation sheets involving subject matter, language, and media experts, as well as teacher and student response questionnaires. The results showed very high feasibility levels, with scores of 98% from subject matter experts, 94.7% from language experts, and 89% from media experts. Teacher and student responses also indicated very good practicality, with scores of 95.9% and 94.4%, respectively. These findings indicate that the developed e-book is feasible and practical to support contextual and literacy-oriented IPAS learning in elementary schools.